A Comparative Grammar of the Early Germanic Languages - R.D. Fulk (Studies in Germanic Linguistics, 2018)
Fulk's Comparative Grammar offers an overview of and bibliographical guide to the study of the phonology and the inflectional morphology of the earliest Germanic languages, with particular attention to Gothic, Old Norse / Icelandic, Old English, Old Frisian, Old Saxon, and Old High German, along with some attention to the more sparsely attested languages. The sounds and inflections of the oldest Germanic languages are compared, with a view to reconstructing the forms they took in Proto-Germanic and comparing those reconstructed forms with what is known of the Indo-European protolanguage. Students will find the book an informative introduction and a bibliographically instructive point of departure for intensive research in the numerous issues that remain profoundly contested in early Germanic language history.